Peruvian earth eaters - Weiss, Pedro (1951)
The habit of eating dirt and limestone ash, which is conserved among people from various parts of Peru, despite centuries of persecution, was apparently a common and natural habit for the Incas. The wide dissemination of this custom among aboriginal Indians were varied as connections of synonyms, and the actual extent of consumption and trade of edible clays, which are sold in the markets of some people, plain or patterned in a silly objects or animals